Relationship of Burnout of Upper Primary School Teachers with Locus of Control - Poonam,; Anuradha, (JOURNAL OF INDIAN EDUCATION, 2014)
This study describes relationship of Burnout with Locus of Control. The study was conducted among upper primary teachers of North-West District of Delhi, which includes 7 Government and 7 private schools of the same area. The numbers of the respondents were 140. The findings revealed that there is a significant relationship between Burnout and Locus of Control of upper primary teachers teaching in Government schools. There is a negative relationship between Burnout and Locus of Control. It means that the teachers having high Burnout Level have an Internal Locus of Control and the teachers having low Burnout level have an External Locus of Control. On the other hand, private schools showed no significant relationship of Burnout with Locus of Control of upper primary teachers teaching in North-West District of Delhi. In terms of Government and private schools, altogether, there is no significant relationship between Burnout and Locus of Control of upper primary teachers teaching in North-West District of Delhi. The Pearson Correlation - Mean, standard deviation and Sig (2 tailed) was applied for statistical analysis by using Statistical Package for Social Sciences (SPSS) to find the relationship of Burnout with Locus of Control.